(untitled) (Ustozlar uchun, 2026)
it is important to note that aligners represent a promising area of orthodontics. With aligners, which are entirely undetectable on the teeth and don’t hurt the patient, modern orthodontics has created a pleasant way to address malocclusion. All of this encourages patients to cooperate and lessens their anxiety about receiving orthodontic treatment, which is becoming more and more popular each year. The suitability of employing detachable transparent aligner trays in place of permanent braces is investigated in this article.